2018
DOI: 10.18632/oncotarget.24059
|View full text |Cite
|
Sign up to set email alerts
|

Distinct expression of CDCA3, CDCA5, and CDCA8 leads to shorter relapse free survival in breast cancer patient

Abstract: Breast cancer is a dangerous disease that results in high mortality rates for cancer patients. Many methods have been developed for the treatment and prevention of this disease. Determining the expression patterns of certain target genes in specific subtypes of breast cancer is important for developing new therapies for breast cancer. In the present study, we performed a holistic approach to screening the mRNA expression of six members of the cell division cycle-associated gene family (CDCA) with a focus on br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
72
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 37 publications
6
72
0
Order By: Relevance
“…The results showed that the OS probability of patients with high expression of CDCA5 and CDCA8 in tumor tissues was significantly decreased. This was consistent with the effect of the two on the survival time of patients in other types of tumors [30][31][32]. Secondly, we analyzed the correlation between the two and all genes involved in the p53 signaling pathway.…”
Section: Discussionsupporting
confidence: 78%
“…The results showed that the OS probability of patients with high expression of CDCA5 and CDCA8 in tumor tissues was significantly decreased. This was consistent with the effect of the two on the survival time of patients in other types of tumors [30][31][32]. Secondly, we analyzed the correlation between the two and all genes involved in the p53 signaling pathway.…”
Section: Discussionsupporting
confidence: 78%
“…Up to now, there is no direct evidence that CDCA5 relates to the initiation and development of any subtype of lung cancer. However, the role of CDCA5 has been confirmed in other cancers including hepatocellular cancer [30], breast cancer [31], gastric cancer [32], and colorectal cancer [33]. Accumulating studies showed that increased CDCA5 level was a diagnostic biomarker and risk factor for numerous cancers which could enhance the tumor cells' capability of proliferation and metastasis by oncogenic ERK5-AP-1 pathway [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the gene H19 (cg21926276 locate) is related with both lung cancer and tumor growth, methylation of which has been thought as a sensitive marker of tobacco history [40,41]. The gene CDCA3 (cg27042065 located) is also associated with lung cancer and survival of cancer patients [42][43][44], and Song and Yang (2018) have reported that gene LOC338797 (cg26387355 located) is related with progression of tumor in lung cancer patients [45]. Besides confirming the previously reported genes, the three CpGs (cg21926276, cg27042065 and cg26387355) are also identified as novel markers for the survival of lung cancer patients.…”
Section: Plos Computational Biologymentioning
confidence: 99%